Rational Framework for the Design of Trp- and Arg-Rich Peptide Antibiotics Against Multidrug-Resistant Bacteria - Xiang, Wenyu; Clemenza, Patrice; Klousnitzer, Jessie; Chen, Jespar; Qin, Weiheng; Tristram-Nagle, Stephanie; Doi, Yohei; Di, Y. Peter; Deslouches, Berthony (Frontiers in Microbiology, 2022)
The threat of antibiotic resistance warrants the discovery of agents with novel antimicrobial mechanisms. Antimicrobial peptides (AMPs) directly disrupting bacterial membranes may overcome resistance to traditional antibiotics. AMP development for clinical use has been mostly limited to topical application to date. We developed a rational framework for systematically addressing this challenge using libraries composed of 86 novel Trp- and Arg-rich engineered peptides tested against clinical strains of the most common multidrug-resistant bacteria known as ESKAPE pathogens. Structure-function correlations revealed minimum lengths (as low as 16 residues) and Trp positioning for maximum antibacterial potency with mean MIC of 2-4µM and corresponding negligible toxicity to mammalian cells. Twelve peptides were selected based on broad-spectrum activity against both gram-negative and –positive bacteria and <25% toxicity to mammalian cells at maximum test concentrations. Most of the selected PAX remained active against the colistin-resistant clinical strains. Of the selected peptides, the shortest (the 16-residue E35) was further investigated for antibacterial mechanism and proof-of-concept in vivo efficacy. E35 killed an extensively-resistant isolate of Pseudomonas aeruginosa (PA239 from the CDC, also resistant to colistin) by irreversibly disrupting the cell membranes as shown by propidium iodide incorporation, using flow cytometry and live cell imaging. As proof of concept, in vivo toxicity studies showed that mice tolerated a systemic dose of up to 30 mg/kg peptide and were protected with a single 5 mg/kg intravenous (IV) dose against an otherwise lethal intraperitoneal injection of PA239. This framework defines the determinants of efficacy of helical AMPs composed of only cationic and hydrophobic amino acids and provides a path for a potential departure from the restriction to topical use of AMPs toward systemic application.